Sowing Methods and Nitrogen Rates Affect Growth and Yield of Sesame in Saline Soil of Southwestern Coastal Bangladesh: Sowing Methods and Nitrogen Rates of Sesame - Akhi, Tanzila Yeasmin; Sarker, Bidhan Chandro; Jahan, Md Sarwar (South Asian Journal of Agriculture, 2025)
A field experiment was conducted at the Regional Inspection Centre (RIC), Bangladesh Meteorological Department, Gollamari, Khulna to study the effect of sowing methods and nitrogen rates on the growth and yield attributes of sesame (BARI Til-6). The experiment comprised of three methods of sowing viz. broadcasting, line sowing and dibbling and four nitrogen levels viz. 0, 15, 30 and 45 kg ha-1 as treatments variables. The experiment was conducted in a Randomized Complete Block Design (RCBD) and replicated thrice. Data were collected on plant height (cm), number of branches plant-1, capsule length (cm), number of capsules plant-1, number of seeds capsule-1, number of seeds plant-1, 1000-seed weight (g), seed weight plant-1 (g), stover weight plant-1 (g) and harvest index (%). For sowing methods, the maximum plant height (60.90 cm), number of branches plant-1 (2.36), number of capsules plant-1 (13.03), number of seeds capsule-1 (52), number of seeds plant-1 (708.33), seed weight plant-1 (1.99 g), stover weight plant-1 (4.12 g), and harvest index (31.10%) were obtained from line sowing method. The lowest plant height (54.85) and seed capsule-1 (49.98) were found in broadcasting whereas, the lowest number of branches plant-1 (1.93), capsule length (1.74 cm), number of capsules plant-1 (9.48), number of seeds plant-1 (497.52), seed weight plant-1 (1.39 g), stover weight plant-1 (3.66 g), and harvest index (27.05%) were obtained from dibbling method. Among the rates of nitrogen, 45 kg N ha‑1 resulted in the highest plant height (69.99 cm), number of branches plant-1 (2.91), capsule length (1.98 cm), number of capsules plant-1 (16.55), and number of seeds capsule-1 (59.15), number of seeds plant-1 (982.42), seed weight plant-1 (2.81 g), stover weight plant-1 (5.50 g), and harvest index (33.60%). Interaction between sowing methods and nitrogen rates significantly influenced all growth and yield attributes except 1000-seed weight (g). The lowest results were found from combination three sowing methods with control treatments. From the findings of the present study, it can be suggested that line sowing with 45 kg N ha-1 may be followed for the cultivation of sesame (BARI Til-6) in the coastal soil of southwestern Bangladesh. South Asian J. Agric. Vol. 11, No. 2, Dec., 2025: 01-13